Formulation of Capsuled Herbal Mixture Using Zingiber officinale and Labisia pumila For Postnatal Care - Pa'ee, Furzani; Idrus, Nurusyuhadah (Enhanced Knowledge in Sciences and Technology, 2021)
Postnatal period is the most critical phase as the tendency for the mother specifically to get illness during the postpartum period is high. In Malaysia, Ministry of Health (MOH) has established the traditional and complimentary medicine (T&CM) to show their support and commitment towards herbal medicine. The aims of this study is to formulate herbal mixture for herbal capsules production based on the traditional knowledge from Temuan community, to analyze phytochemicals of the herbal mixture and to develop herbal medicine in the form of capsules. There were five formulations of Zingiber officinale (Ginger) and Labisia pumila (Kacip Fatimah) mixtures which had been designed by Design Expert software. Total flavonoid content and antioxidant content of the herbal mixtures were analyzed by using aluminum chloride colorimetric assay and DPPH assay, respectively. The result shows that the mixture with ratio 1 of Zingiber officinale to 3 of Labisia pumila contained high flavonoid content while, mixture with ratio 1 of Zingiber officinale to 1 of Labisia pumila contained high antioxidant content. Hence, those mixtures were being used to be developed as herbal medicine in the form of capsules using capsule filling machine. The moisture content and disintegration test of the capsules were evaluated for their quality control.